Impairment of an atrophic mandible by preparation of the implant cavity: a biomechanical study. Issue 6 (July 2016) - Steiner, Timm; Torsiglieri, Tobias; Rau, Andrea; Möhlhenrich, Stephan C.; Eichhorn, Stefan; Grohmann, Isabella; Deppe, Herbert; Hölzle, Frank; Raith, Stefan
Abstract: An important complication during insertion of implants in atrophic mandibles is the fracture that can be induced by preparation of the cavity. We designed this study to identify which configuration of cavities in the interforaminal region was the least likely to fracture. An electromechanical testing machine was used to measure breaking loads of specifically-designed synthetic models of atrophic mandibles. The implant cavities correlated with the common clinical patterns. Intact atrophied synthetic mandibles broke at a mean (SD) load of 729.48 (59.94) N (control group). Models with four different configurations of cavities fractured as follows: two short, wide cavities (8 x 4.2 mm) at a mean (SD) load of 569.17 (67.7) N; two long, thin cavities (15 x2.8 mm) at a load of 563.40 (62.0) N; four short, wide cavities (8 x 4.2 mm) at a load of 667.01 (71.89) N; and four long, thin cavities (15 x 2.8 mm) at a load of 409.50 (43.61) N. Biomechanical findings showed that there was a greater risk of fracture of atrophic mandibular models in long, thin implant cavities with more preparation sites. Each cavity prepared for an implant increased the risk of fracture in an atrophic mandible. The risk of fracture is greatest with long, thin cavities.